Sharing economy, technological innovation and carbon emissions: Evidence from Chinese cities - Jiafeng Gu (Journal of Innovation & Knowledge (JIK), 2022)
The development of the sharing economy offers opportunities to reduce urban carbon emissions. Unfortunately, few studies have examined the impact of the sharing economy on urban carbon emissions from a holistic view based on the integration of local and neighborhood hierarchies. This paper examines the impact of the sharing economy on urban carbon emissions from 2011 to 2017 using a sample of 275 prefecture-level cities in China. The results show that the development of personal credit information services and digital finance both contribute to curbing urban carbon emissions. Technological innovation is not only beneficial to urban carbon emission reduction, but also has a negative moderating effect on the relationship between economic development and carbon emissions. Spatial spillover effects of the sharing economy help curb carbon emissions in neighboring cities. Finally, policy recommendations are presented to promote the collaborative economy and reduce urban carbon emissions.
Keywords: R58; Q55; Q56; 650; Sharing economy; Carbon emission; City; Spatial spillover; Technological innovation